A signature of circulating microRNAs differentiates takotsubo cardiomyopathy from acute myocardial infarction - Jaguszewski, Milosz; Osipova, Julia; Ghadri, Jelena-Rima; Napp, Lars Christian; Widera, Christian; Franke, Jennifer; Fijalkowski, Marcin; Nowak, Radoslaw; Fijalkowska, Marta; Volkmann, Ingo; Katus, Hugo; Wollert, Kai C.; et al. (European heart journal, 2014)
Takotsubo cardiomyopathy (TTC) remains a potentially life-threatening disease, which is clinically indistinguishable from acute myocardial infarction (MI). Today, no established biomarkers are available for the early diagnosis of TTC and differentiation from MI. MicroRNAs (miRNAs/miRs) emerge as promising sensitive and specific biomarkers for cardiovascular disease. Thus, we sought to identify circulating miRNAs suitable for diagnosis of acute TTC and for distinguishing TTC from acute MI.
Online publish-ahead-of-print 17 September 2013
Gesehen am 09.09.2020